Influence of trail running footwear foam on running economy and perceptual metrics - Muzeau, M.; Flood, A.; Tam, N.; Abel, B.; Saunders, P.; Staiano, W.; Rattray, B. (European Journal of Sport Science, 2025)
Advanced footwear technologies (AFT) improve road running performance. AFT have been incorporated into trail running footwear despite little evidence of their benefits in this context. In this study, we compared the effect of traditional (TRADI-f) and AFT foam (AFT-f) on running economy and perceptual measures across different gradients. Fourteen well-trained athletes completed assessments on a treadmill at gradients of FLAT (0% gradient, 14 km.h-1), UP (+10%, 8 km.h-1) and DOWN (-10%, 14 km.h-1). Two shoes were randomly allocated in a counterbalanced order. The shoes were matched in construction but differed in midsole foam performance, where the AFT-f shoe included a more compliant and resilient foam than the TRADI-f shoe. Oxygen consumption and heart rate were collected for 6 min, twice with each shoe at each gradient, alongside perceived effort and affective measures. Across the three gradients, oxygen consumption was 1.2% lower (p = 0.008) when participants were wearing the AFT foam compared to the TRADI foam. The effect of the AFT-f shoes on oxygen consumption appeared to be more pronounced in the FLAT (+2.1%) and UP (+1.0%) conditions compared to DOWN (+0.2%). This interaction effect was, however, not statistically significant (p = 0.050). RPE was lower (p = 0.008) and affective valence more positive (p = 0.027) in AFT-f compared to TRADI-f. No differences in arousal were reported between TRADI-f and AFT-f (p = 0.728). The findings of this study suggest that an AFT foam in trail running shoes can improve running economy, reduce perceived effort and increase pleasure while running in a trained athlete population.